Problemele dezvoltării proceselor inovatoare în gospodăriile agricole din Republica Moldova [Articol] - Balînschi, Andrei (USARB, 2017)
The problems of the scientific definition of the term „innovation” are being examined; the value of innovation for the agricultural sector of economy of the Republic of Moldova is being determined. Examples of innovations in small and medium farms in the Republic of Moldova through international projects financed by the EU are being presented. The effectiveness of the implementation of the project „Establishment and promotion of new approaches and tools for the strengthening of primary sector’s competitiveness and innovation in the South East Europe” (APP4INNO) in the Republic of Moldova is being analyzed.
Keywords: innovative product; ecological balance; inovaţii în agricultură